PROSES KOLABORASI DALAM PENINGKATAN PEREKONOMIAN MELALUI PROGRAM ADI MARKO (AUDIENSI INKUBASI DAN MARKETING ONLINE) DI KABUPATEN BLITAR: (Studi pada Dinas Perindustrian dan Perdagangan Kabupaten Blitar) - Permatasari, Cindy Eka (Jurnal Administrasi Publik, 2024)
Collaborative Process In Improving The Economy Through ADI MARKO Progam  (Incubation Audience  and Online Marketing) at Blitar Regency. Studi at Blitar District Industry and Trade Department. The Blitar Regency Government has a digital marketing training program known as ADI MARKO (Online Incubation and Marketing Audience). The training was held because of the current challenges of the digital economy and to support the implementation of Smart Economy conditions in Blitar Regency. As for its implementation, the government involves stakeholders such as the private sector, academics, mass media and the public to collaborate in implementing the program. The objectives of the research are 1) To understand and analyze the collaboration process carried out by the government in implementing the ADI MARKO program to improve the economy in Blitar Regency. 2) Know and analyze the supporting and inhibiting factors of the ADI MARKO (Online Incubation and Marketing Audience) program. This research uses descriptive research methods with a qualitative approach. The research results show that the collaborative process aspect by Ansel and Gash (2007) can provide maximum collaboration processes for the government, because from this collaboration ADI MARKO program participants are able to apply digital marketing knowledge in their businesses.